Selectivity in early prosocial behavior - Kuhlmeier, Valerie A.; Dunfield, Kristen A.; O’Neill, Amy C. (Frontiers in Psychology, 2014)
Prosocial behavior requires expenditure of personal resources for the benefit of others, a fact that creates a “problem” when considering the evolution of prosociality. Models that address this problem have been developed, with emphasis typically placed on reciprocity. One model considers the advantages of being selective in terms of one’s allocation of prosocial behavior so as to improve the chance that one will be benefitted in return. In this review paper, we first summarize this “partner choice” model and then focus on prosocial development in the preschool years, where we make the case for selective partner choice in early instances of human prosocial behavior.